Gamification: A Pilot Study in a Community College Setting. Issue 2 (April 2019) - O'Connor, Patrick; Cardona, Josué
Gamification has been used as a tool to increase engagement with businesses, build group cohesion, and improve student motivation in Grades K-12. Part of its appeal is in developing autonomy in the "player, " and part of its appeal is in participating regularly in a structured progress ladder where the customer, student, or employee can predict how present actions can lead to future rewards. Currently, research in applying gamification to undergraduate courses is sparse, which is surprising given the overlap between higher education and game design; students and players both follow rules, participate voluntarily, engage with a feedback loop, and work toward a goal. This study applied game design principles via gamification to an undergraduate General Psychology course at a community college. Results indicate better motivation, improved exam scores, a stronger sense of autonomy, and a desire within students to have more courses offered in this manner. However, final course grades showed no significant difference compared with traditionally designed courses. Implications for future research are discussed.